2012
DOI: 10.1039/c2cc30188a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high-quality carbon nanodots from hydrophilic compounds: role of functional groups

Abstract: A simple one-pot hydrothermal approach has been demonstrated for the preparation of highly water soluble and photoluminescent carbon nanodots (C-dots) from low-cost organic compounds. We found that the compounds incorporating amino and carboxylic acid groups are suitable for the preparation of highly photoluminescent and water-soluble C-dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
296
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 490 publications
(309 citation statements)
references
References 41 publications
10
296
0
3
Order By: Relevance
“…C-dots have been synthesized from citric acid [2], candle soot [5], soy milk [4], egg white and egg yolk [6], gum arabic [7], orange peel 8], and various amino acids [9]. Hsu et al [10] observed that functional groups of carboxylic acid and hydroxylate on the starting material of organic compounds are very important in the synthesized of C-dot. There are two methods to synthesizing C-dots, the bottom-up and the top-down methods.…”
Section: Introductionmentioning
confidence: 99%
“…C-dots have been synthesized from citric acid [2], candle soot [5], soy milk [4], egg white and egg yolk [6], gum arabic [7], orange peel 8], and various amino acids [9]. Hsu et al [10] observed that functional groups of carboxylic acid and hydroxylate on the starting material of organic compounds are very important in the synthesized of C-dot. There are two methods to synthesizing C-dots, the bottom-up and the top-down methods.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the synthetic methods for C-dots include arcdischarge [2], electrochemical oxidation [3][4][5], laser ablation [6][7][8][9], hydrothermal synthesis [10][11][12][13][14][15], pyrolysis [16][17][18][19], microwave-assisted heating [20][21][22][23][24][25][26], plasma treatment [27], neutralization heating [28], and sonication treatment [29] (Scheme 1). All these synthetic methods allow, up to some extent, preparing moderately high-quality C-dots with relatively high PL performance and small size.…”
Section: Introductionmentioning
confidence: 99%
“…The gradual decrease observed at pH 1 -3 was ascribed to the decrease in the density of deprotonated carboxylic acids functionality on the CND surface. 21 These results suggest the high dispersibility of the CNDs in a wide range of aqueous solutions.…”
Section: Resultsmentioning
confidence: 69%